1977
DOI: 10.1136/jmg.14.6.399
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of family history data for evidence of non-Mendelian inheritance resulting from vertical transmission.

Abstract: SUMMARY A number of infections of man, as well as of other animal and plant species, are heavily dependent upon 'vertical transmission'-that is direct parent-to-progeny transfer-for their maintenance in host populations. Such vertical transmission may be considered as a form of inheritance. It is usually non-Mendelian. This paper discusses the implications of such inheritance for the distribution of disease in families. A method is described for making quantitative predictions of prevalence rates of infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…First, family members sharing a common environment may be more likely than unrelated persons to have common exposure to an infectious agent or to transmit the agent to each other through personal contact. It has been shown that with this mechanism a pattern of maternal transmission, such as that we have observed, is expected (16) . Second, there may be an inherited susceptibility to infection by a relevant organism.…”
Section: Discussionmentioning
confidence: 58%
“…First, family members sharing a common environment may be more likely than unrelated persons to have common exposure to an infectious agent or to transmit the agent to each other through personal contact. It has been shown that with this mechanism a pattern of maternal transmission, such as that we have observed, is expected (16) . Second, there may be an inherited susceptibility to infection by a relevant organism.…”
Section: Discussionmentioning
confidence: 58%
“…Several genetic models have been considered in an effort to develop methods for testing this possibility of non-Mendelian maternal transmission [Fine, 1977;Boehnke et a]., 19831.…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches extend traditional genetic and aggregation models to specifically model transmission. 48,49 As mentioned earlier, some of the known or suspected risk factors in periodontal disease etiology are age, race, gender, socioeconomic status, genetics, periodontal microbes, comorbidities (systemic disease, diabetes, etc. ), dental hygiene, diet and nutrition, tobacco use (cigarette, cigar, pipe), alcohol, osteopenia, osteoporosis, psychosocial factors (stress, distress, coping behaviors), and polymorphonuclear leukocyte disorders.…”
Section: Statistical Analysis Of Family Datamentioning
confidence: 99%
“…Athough not described in detail here, the original model of Fine 48 permits inclusion of a net horizontal incidence rate covering the period from birth to reproductive age to allow for the possibility of supplemental horizontal transfer. Such horizontal transmission may be necessary to maintain infection within a host population; it is possible to define the extent of such horizontal transmission required to maintain equilibrium prevalence.…”
Section: Transmission Models-vertical Environmental Transmissionmentioning
confidence: 99%